2018
DOI: 10.1021/acs.molpharmaceut.8b00717
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cancer Immunochemotherapy via Optimal Co-delivery of Chemotherapeutic and Immunomodulatory Agents

Abstract: It is highly demanded and still a big challenge to develop an effective formulation for immunochemotherapy against advanced tumors. We have previously reported a PEG-NLG-based immunostimulatory nanocarrier (PEG-Fmoc-NLG919) for co-delivery of an IDO1 inhibitor (NLG919) and a chemotherapeutic agent (paclitaxel, PTX). Although antitumor immune responses were enhanced with a PTX-loaded nanocarrier, the accumulation of myeloid-derived suppressor cells (MDSCs) was also significantly increased, which may limit the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 63 publications
(165 reference statements)
0
24
1
Order By: Relevance
“…These micelles, whether loaded with DOX or not, reduced the recruitment of granulocytic MDSC and monocytic MDSCs to tumor tissues. This contrasts with the observation that the same micelles, when loaded with PTX, triggered the counter-productive accumulation of MDSCs (Chen et al, 2018). These differences may reflect the different abilities of DOX and PTX to modulate the immune system.…”
Section: Peg-derivatized Dual-functional Micelles For Immunochemo-thecontrasting
confidence: 88%
See 1 more Smart Citation
“…These micelles, whether loaded with DOX or not, reduced the recruitment of granulocytic MDSC and monocytic MDSCs to tumor tissues. This contrasts with the observation that the same micelles, when loaded with PTX, triggered the counter-productive accumulation of MDSCs (Chen et al, 2018). These differences may reflect the different abilities of DOX and PTX to modulate the immune system.…”
Section: Peg-derivatized Dual-functional Micelles For Immunochemo-thecontrasting
confidence: 88%
“…Increased numbers of tumor-infiltrating MDSCs often correlate with high tumor burden and metastasis, contributing to poor prognosis (Nagaraj and Gabrilovich, 2008; Malek et al, 2016). To avoid stimulating MDSCs, a dual-functional carrier of PEG linked to NLG919 via an Fmoc moiety was loaded with both PTX and sunitinib (Chen et al, 2018), an FDA-approved tyrosine kinase inhibitor for the treatment of various cancers. Sunitinib reduces the level and activity of MDSCs and Treg cells systemically and in the tumor microenviroment (van Hooren et al, 2016; Motzer et al, 2017).…”
Section: Peg-derivatized Dual-functional Micelles For Immunochemo-thementioning
confidence: 99%
“…The production of chemokines responsible for the recruitment of MDSCs was drastically blocked by sunitinib and helped improve the overall efficiency of the combination therapy. [ 73 ] The recent studies from Rivas's group fabricated phospholipids based micellar nanocarrier to integrate the TLR 4 agonist Xcc lipooligosaccharide, OVA antigen, and iron oxide nanoparticles to facilitate the co‐delivery of immune stimulators. The TLR agonist Xcc lipooligosaccharide induced the immune response by secreting costimulatory molecules on DCs and inflammatory cytokines (TNF‐ α and IL‐12) and helps in creating an immunogenic environment.…”
Section: Self‐assembled Multifunctional Nanomaterials For Combinatorimentioning
confidence: 99%
“…Other studies have also confirmed that nanomaterials effectively enhance the immunomodulatory effect of sunitinib, and the combination of sunitinib and other drugs achieved better antitumor effects. 92,93 The CSF-1/CSF-1R Pathway Colony stimulating factor-1 (CSF-1) is a cytokine that plays an important role in the survival, proliferation, differentiation, and function of macrophages. 94 Studies have shown that CSF-1 is highly expressed in some tumors and is associated with poor prognosis and distant metastasis.…”
Section: Modulating the Immunosuppressive Tmementioning
confidence: 99%